SANDSTONE RESERVOIR CHARACTERIZATION BASED ON FACIES ANALYSIS AND PETROPHYSICAL ROCK TYPE OF D-17A ZONE, BALIKPAPAN FORMATION, SANGA-SANGA BLOCK, KUTAI BASIN, EAST KALIMANTAN - GRIFTHIANA RAHMADITA - NIM: 22014315, DITTA
Simerah Field was firstly discovered in 1974. Simerah Field is located in the northern edge part of Mahakam Delta, Kutai Basin, East Kalimantan. This field is one of the main producer hydrocarbon field, especially gas. Recently, this field is in development and production phase. One of the main gas reservoir in this field is D-17A Zone, Balikpapan Formation. In case of gas field development, flow unit is required to know production performance from interval which canÃ‚Â’t be predicted only by porosity data. Therefore, the solution that would be perform is the detail analysis of reservoir characteristic through lithofacies and petrophysical Rock Type (RT) approaches. Several data which have been used in this research are core data of D-17A Zone from two wells with 95 ft in total length, log data from 48 wells, and seimic 2D data. Based on core analysis, D-17A Zone was deposited in distributary channel facies and consist of six lithofacies, namely: claystone (Fl), horizontal lamination very fine-medium sandstone (Sh), ripple cross lamination fine sandstone (Sr), flasser bedding fine sandstone (Sf), medium planar cross lamination sandstone (Sp), and structureless medium sandstone (Ssl). Rock type identification uses FZI (Flow Zone Indicator) approach, was performed with plotting of 215 Routine Core Analysis (RCAL) samples. As the results, D-17A Zone is devided into several types of RT, which RT 1 is the best in fluid flow identification and RT 4 is the worst in fluid flow identification. Each of rock type has a good correlation between porosity and permeablity with correlation coefficient value as follows RT 1 = 0.75; RT 2 = 0.7; RT 3 = 0.85; and RT 4 = 0.77. Moreover, this research conclude that one of facies could be consist of several RT, and one of rock type could be occured by several lithofasies in D-17A Zone.